1984
DOI: 10.1128/mcb.4.6.1003
|View full text |Cite
|
Sign up to set email alerts
|

Identification, purification, and characterization of phosphotyrosine-specific protein phosphatases from cultured chicken embryo fibroblasts.

Abstract: Tyrosine phosphorylation catalyzed by a unique class of protein kinases is an important process in both normal cell proliferation and oncogenic transformation. In this study, phosphoprotein phosphatases specific for the dephosphorylation of phosphotyrosine residues were partially purified from secondary chicken embryo fibroblasts, using 32P-labeled immunoglobulin G phosphorylated by pp6fyrc as substrate. Crude cell extracts contained ca. 70% of the activity in the soluble form and ca. 30% associated with a cru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
1

Year Published

1986
1986
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(48 citation statements)
references
References 46 publications
3
44
1
Order By: Relevance
“…These studies did not, however, exclude a contribution of calmodulindependent protein phosphatase to the phosphotyrosylprotein phosphatase activity, because comparative measurements were not made under conditions whereby calmodulin-dependent protein phosphatase was highly active (Brautigan et al, 1981;Foulkes et al, 1983;Chernoff & Li, 1983;Shriner & Brautigan, 1984). Although Foulkes et al (1983) Li, 1983;Shriner & Brautigan, 1984;Okada et al, 1986) and found no more than 36-45 % of the phosphatase in membrane fractions (Martensen, 1982;Nelson & Branton, 1984;Rotenberg & Brautigan, 1987). This difference may be attributable to the use of non-specific artificial substrates in the previous studies, whereas specific receptor substrates have been utilized in the present work.…”
Section: Phosphotyrosylcontrasting
confidence: 48%
“…These studies did not, however, exclude a contribution of calmodulindependent protein phosphatase to the phosphotyrosylprotein phosphatase activity, because comparative measurements were not made under conditions whereby calmodulin-dependent protein phosphatase was highly active (Brautigan et al, 1981;Foulkes et al, 1983;Chernoff & Li, 1983;Shriner & Brautigan, 1984). Although Foulkes et al (1983) Li, 1983;Shriner & Brautigan, 1984;Okada et al, 1986) and found no more than 36-45 % of the phosphatase in membrane fractions (Martensen, 1982;Nelson & Branton, 1984;Rotenberg & Brautigan, 1987). This difference may be attributable to the use of non-specific artificial substrates in the previous studies, whereas specific receptor substrates have been utilized in the present work.…”
Section: Phosphotyrosylcontrasting
confidence: 48%
“…Recent evidence suggests that tyrosine kinase phosphorylation could be regulated by a diverse family of enzymes referred to as protein tyrosine phosphatases (PT-Pax) [3,4], whose catalytic activity is dependent on a specific cysteine residue [5]. PTPase activity is found associated with the plasma membrane and/or in the cytosol [6]. Their specific activities are much greater than protein tyrosine kinases .xrd they therefore have thecapacity to regulate the levei of tyrosine phosphorylation of proteins involved in signal transduction pathways in the cell [7].…”
Section: Introductionmentioning
confidence: 99%
“…1 and 3). Sodium orthovanadate, the prototype PTPase inhibitor (24,25), has also been shown to interact with the cysteine residue within covalent bond distance (26). Peroxovanadate (a mixture of orthovanadate and hydrogen peroxide) oxidizes the cysteine by forming cysteic acid (26), whereas alendronate forms sulfonic acid with the cysteine (27), and aromatic disulfides (28) and nitric oxide (29) form disulfides and inactivate the enzyme activity.…”
Section: Effects Of Cpd 5 On Cell Growth and Protein-tyrosine Phosphomentioning
confidence: 99%